APLIKASI TAJWID BERBASIS ANDROID - ANDRIA, KIKI; Handoko, Koko (LPPM Universitas Putera Batam, 2021)
abstrack Along with the development of technology in this era is increasingly advanced and rapid so that it can make it easier for people to create various types of applications to create learning media and to help daily activities. In Islam, reading alqur'an has certain rules called tajwid. Tajwid is a science that learns about how to read and pronounce the letters contained in the Holy Qur'an. Tajwid learning is useful for improving how to properly pronunciation alqur'an. There is still a lack of learning media about the science of tajwid and the existing learning system is still raw and boring. The method used in designing android-based tajwid application uses Agile and UML (Unified Modeling Language) methods and the software used are React Native, Node Js, NPM (Node Package Manager), JDK (Java Development Kit), Android SDK (Software Development Kit), Microsoft Visio. The results obtained from this study are in the form of android-based tajwid application. At the testing stage tajwid application using black box testing. From the test results showed that each menu made was able to be accessed easily and run well. so that the results of this research, it can be concluded that the android-based tajwid application becomes an interesting learning media and tdiak boring, making it easier for children, especially Muslims in learning the science of tajwid.